Assessment of stressful life events for patients with substance abuse in Baghdad city - Shakhat, ali; hashim, Mushatq (Iraqi National Journal of Nursing Specialties, 2013)
Objective: The present study aims to assess the stressful life events for patients with substance abuse in Baghdad city. Methodology: A descriptive study was carried out at (Baghdad teaching hospital and Ibn-Rushed Psychiatric hospital). Starting from 1 st of December 2012 to 3 rd of July 2013, A non-probability (purposive) sample of 64 patients that diagnosed with substance abuse, the data were collected through the use of semi-structured interview by questionnaire, which consists of three parts sociodemographic data, medical information, and Life events scale consists of 49-items distributed to six domains including, family and social domain, health domain, security, legal and criminal domain, work and school domain, financial domain, and change of residence domain. A pilot study was carried out to determine the questionnaire reliability through the use of (Cronbach alpha). Validity of the instrument was established through penal of (13) experts. Data was analyzed by application of descriptive and inferential statistical methods. Results: The study findings revealed that all sample (100%) are males, and about half of sample were at age (20-29) years, (50.8%) of them had completed primary school, married, unskilled worker, and more than two third- of them were living in urban area. Health domain and family and social domain had more effects on patients than other domains. Recommendations: Increase the individual awareness about management of the stressful life events to decrease the impact of life events upon their Psychological health